Experimental Study on Durability Properties of Ambient Cured Fly Ash and GGBFS Based Geopolymer Concrete with Addition of Lime - Patel, Bansalkumar R.; Patel, Harshvadan S. (International Journal of Membrane Science and Technology, 2022)
As the tremendous use of cement for construction, the Ordinary Portland Cement (OPC) production increases day by day. The cement production is held responsible for CO2 emissions, which polluted the atmosphere. Hence, it is inevitable to find an alternative material to OPC. The geopolymer concrete is a best alternative which shall be produced by the chemical action of inorganic molecules. This paper focuses on fly-ash based Geopolymer concrete with addition of hydrated lime. In the geopolymer concrete, cement is completely replaced by fly ash, ground granulated blast furnace slag (GGBFS) and hydrated lime. A solution of Sodium Hydroxide (NaOH) and Sodium Silicate (Na2SiO3) was used as an alkaline solution with Na2SiO3: NaOH ratio 2.0. The hydrated lime is used with variation in GGBFS replacement with percentiles as 5%, 10%, 15% and 20%. The GPC samples were cured at ambient temperature (27± 2?) for 7 days and 28 days and then tested for compressive strength. Slump cone test on fresh mixes were also performed. The optimized geopolymer concrete with the best workability and compressive strength, was chosen, and the specimens of standard sizes were casted and tested for acid attack of ????2????????4, HCl and NaCl. Also, the sorptivity test and the abrasion value test were performed to compare the density of concrete.